Meningkatkan Minat Belajar Anak Taman Kanak-kanak melalui Pembelajaran di Luar Kelas - Wahyuni, Sri; Handayani, Arri; Rakhmawati, Dini (Medan Resource Center, 2024)
This study explores the impact of outdoor learning activities on increasing children's interest in learning, both physically and mentally. The focus is on early childhood education, emphasizing active creation and experiential learning over traditional lecture methods. This approach encourages children to learn from their own experiences and form conclusions based on their own observations and thoughts. The research investigates how taking students outside the classroom for teaching enrichment provides them with unique learning experiences unavailable within the confines of a traditional classroom setting. By engaging with their environment, students gain opportunities to observe and experience firsthand, fostering a deeper understanding and interest in the subjects taught. The methodology includes observational studies and qualitative analysis of students' responses to outdoor learning activities. Results indicate that learning outside the classroom significantly enhances children's engagement and enthusiasm for learning. This study concludes that incorporating outdoor learning into early childhood education can provide substantial benefits, enriching students' educational experiences and supporting their overall development.